Fully aromatic naphthalene-based sulfonated poly(arylene ether ketone)s with flexible sulfoalkyl groups as polymer electrolyte membranes. Issue 1 (1st December 2014) - Wang, Baolong; Cai, Zhenzhen; Zhang, Na; Zhang, Bin; Qi, Duo; Zhao, Chengji; Na, Hui
Abstract : Naphthalene-based poly(arylene ether ketone)s with pendant sulfoalkyl groups were prepared by a demethylation and sulfobutylation method. They exhibited high proton conductivity, low methanol permeability and high thermal stability. Abstract : A series of sulfonated naphthalene-based poly (arylene ether ketone)s (SNPAEK-xx) with pendant sulfoalkyl groups were prepared by polycondensation of 1, 5-bis(4-fluorobenzoyl)-2, 6-dimethoxynaphthalene and o -methylhydroquinone, followed by a demethylation and sulfobutylation reaction. The sulfonate degree of SNPAEK-xx could be controlled easily by adjusting the ratio of 1, 4-butane sultone to the hydroxyl content in the demethylated polymers. Flexible and tough membranes with reasonably high mechanical strength were prepared. SNPAEK-xx membranes showed a high ionic exchange capacity (IEC) in the range of 1.13 to 2.27 mequiv. g −1, and the highest proton conductivity of 0.191 S cm −1 at 80 °C. They exhibited low methanol permeability in the range of 1.25–10.22 × 10 −7 cm 2 s −1, which was much lower than that of Nafion 117. Transmission electron microscopy analysis of SNPAEK-xx revealed that they had a more obvious phase separated structure between the hydrophilic side chain and hydrophobic fully aromatic domains at a higher IEC. Combining their high thermal and mechanical stability, high selectivity, lower water swelling ratio, SNPAEK-xx membranes could be promising materials as alternative to Nafion membranes for direct methanol fuel cell applications.